Effect of Anacetrapib on Cholesterol Efflux Capacity: A Substudy of the DEFINE Trial - Metzinger, Mark P. (J Am Heart Assoc, 2020)
BACKGROUND: Anacetrapib is the only cholesteryl ester transfer protein inhibitor proven to reduce coronary heart disease (CHD). However, its effects on reverse cholesterol transport have not been fully elucidated. Macrophage cholesterol efflux (CEC), the initial step of reverse cholesterol transport, is inversely associated with CHD and may be affected by sex as well as haptoglobin copy number variants among patients with diabetes mellitus. We investigated the effect of anacetrapib on CEC and whether this effect is modified by sex, diabetes mellitus, and haptoglobin polymorphism. METHODS AND RESULTS: A total of 574 participants with CHD were included from the DEFINE (Determining the Efficacy and Tolerability of CETP Inhibition With Anacetrapib) trial. CEC was measured at baseline and 24‐week follow‐up using J774 macrophages, boron dipyrromethene difluoride–labeled cholesterol, and apolipoprotein B–depleted plasma. Haptoglobin copy number variant was determined using an ELISA assay. Anacetrapib increased CEC, adjusted for baseline CEC, risk factors, and changes in lipids/apolipoproteins (standard β, 0.23; 95% CI, 0.05–0.41). This CEC‐raising effect was seen only in men (P interaction=0.002); no effect modification was seen by diabetes mellitus status. Among patients with diabetes mellitus, anacetrapib increased CEC in those with the normal 1‐1 haptoglobin genotype (standard β, 0.42; 95% CI, 0.16–0.69) but not the dysfunctional 2‐1/2‐2 genotypes (P interaction=0.02). CONCLUSIONS: Among patients with CHD, anacetrapib at a dose linked to improved CHD outcomes significantly increased CEC independent of changes in high‐density lipoprotein cholesterol or other lipids, with effect modification by sex and a novel pharmacogenomic interaction by haptoglobin genotype, suggesting a putative mechanism for reduced risk requiring validation.